Novel Use of Smartphone-based Infrared Imaging in the Detection of Acute Limb Ischaemia. (2016) - Peleki, A.; da Silva, A.
Abstract : Introduction: Infrared thermal imaging is based on perfusion changes reflected by skin temperature variations. It is an established non-invasive diagnostic method within vascular surgery, with applications such as peripheral arterial disease assessment and prevention of diabetic foot complications. However, owing to hardware limitations or lack of resources, it is not yet widely used in clinical practice. Report: A novel portable infrared imaging camera, easily powered via a smartphone and free App software, was used to obtain digital thermograms during the clinical evaluation of acute limb ischaemia (ALI). Discussion: Portable infrared imaging represents a new promising tool for the assessment of tissue perfusion that can be applied at the bedside during clinical evaluation of suspected ALI. Highlights: Infrared imaging is an established diagnostic tool in peripheral arterial disease. A novel portable infrared camera is introduced in the assessment of acute limb ischaemia. Thermograms are taken to demonstrate perfusion discrepancy between two limbs. Good diagnostic adjunct prior to initiation of treatment in acute limb ischaemia. Valuable baseline perfusion imaging for evaluation of revascularisation results.